Pengaruh Pengetahuan Keuangan, Sikap Keuangan, Dan Kepribadian Terhadap Perilaku Manajemen Keuangan Bagi Pelaku UMKM Industri Kuliner Di kelurahan Merjosari - Muttaqin, Fatih Sahirul; Farida, Eka; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this research is to explore the extent to which financial knowledge, attitudes, and personality traits influence financial management behavior within the culinary MSME sector in Merjosari Subdistrict, Malang City. Using a quantitative method with an explanatory research approach, data were collected from 93 respondents Slovin’s formula was applied to determine the sample size, followed by the application of random sampling for respondent selection. Data analysis was carried out through the application of multiple linear regression techniques. Results indicated that all three variables simultaneously have a significant influence on financial management behavior. Partially, financial knowledge has the most dominant influence, followed by financial attitudes and personality both contribute positively and significantly to financial behavior. These findings emphasize the importance of enhancing financial literacy and attitudes, as well as fostering personality traits that support better financial management among MSMEs. Keywords: Financial Knowledge, Financial Attitude, Personality, Financial Management, Culinary MSMEs.